Cerebral venous thrombosis and the eye: the neuro-ophthalmology of cerebral venous blood clot - Mishra, Ashutosh Kumar; Shukla, Ruchi; Verma, Archana; Chaurasia, Rameswar Nath (Nepal Journal of Neuroscience, 2024)
Introduction: Cerebral venous thrombosis (CVT) is a form of venous thromboembolism which has varied clinical presentation. Ocular clinical features are quite common in CVT and may be the sole presenting feature and often tend to get misdiagnosed. This study was conducted to analyse clinical features especially neuro ophthalmological manifestations in CVT patients. Materials and Methods: In this prospective study 60 patients were enrolled in a study period of 3 years at tertiary care hospital. Follow up visits were performed at 1 month, 3 months, 6 months and 12 months after the initial diagnosis. We analysed the clinical features as well as aetiology of CVT, special focus was on the ocular symptoms and signs. Results: Headache was the most common clinical symptom with 93.33% patients. Among ocular symptoms 43.33 % patients presented with complaint of blurring of vision. Among ophthalmological signs papilledema was reported in 40.0 % patients, cranial nerve involvement in 10.0 % patients, diplopia was seen in 6.66 % patients. In patients with papilledema the intensity reduced as time progressed. Vision loss was seen in 2 patients who had secondary optic atrophy. Conclusion: To avoid misdiagnosis and for the prevention of vision deterioration the ophthalmologist must pay attention to CVT symptoms and signs when patients present with ocular symptoms as the initial manifestation.